Fundamentals of embryology : methodical guidance for the 1st academic year students of the School of Medicine [Electronic resource] - Protsenko, Olena; Chumak, Lyubov; Проценко, Олена Сергіївна; Чумак, Любов Ігорівна (Kharkiv : V. N. Karazin Kharkiv National University, 2025)
Methodological guidance contains basic recommendations for preparing first-year medical students for classes and exams in the elective discipline “Fundamentals of Embryology”. Developed for applicants for higher medical education in higher medical educational institutions of Ukraine III-IV accreditation levels: higher educational level Second (Master of Medicine), field of knowledge “22 Healthcare”, specialty “222 Medicine”, qualification “Doctor”.

Методичні рекомендації містять основні рекомендації щодо підготовки студентів I курсу медичного факультету до занять, заліку із дисципліни за вибором студента «Основи ембріології» і призначені здобувачам вищої медичної освіти у вищих медичних навчальних закладах освіти України ІІІ-ІV рівнів акредитації: спеціальність «222 Медицина», галузь знань «22 Охорона здоров’я», кваліфікація «Лікар».
Основи ембріології : методичні рекомендації для студентів I курсу медичного факультету [Електронний ресурс]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі. В авторській редакції
Keywords: SOCIAL SCIENCES::Social sciences::Education::Subject didactics; MEDICINE::Morphology, cell biology, pathology; основи ембріології; медицина; fundamentals of embryology; medicine